2018
DOI: 10.1037/fam0000446
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between parent-child relationships in middle childhood and child-perceived loneliness.

Abstract: Loneliness may affect children's psychological well-being and academic achievement. Parent-child relationships have been consistently associated with child adjustment. However, parental antecedents of child loneliness have been relatively understudied. Guided by attachment theory, we examined the trajectories of father-child and mother-child relationship closeness and conflict, and their associations with trajectories of child loneliness with National Institute of Child Health and Human Development (NICHD) Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…This finding is consistent with Lewin's field theory, which suggested the fundamental elements of people's behaviors were the result of undisrupted interactions between individuals and their surroundings [96]. On top of that, it was confirmed that loneliness could affect the mental health and academic performances of individuals and was related to parent-child relationship [97]. In this connection, we can confirm that loneliness can mediate the link between parent-child relationship and smartphone addiction, and the finding also coincides with the previous empirical studies.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…This finding is consistent with Lewin's field theory, which suggested the fundamental elements of people's behaviors were the result of undisrupted interactions between individuals and their surroundings [96]. On top of that, it was confirmed that loneliness could affect the mental health and academic performances of individuals and was related to parent-child relationship [97]. In this connection, we can confirm that loneliness can mediate the link between parent-child relationship and smartphone addiction, and the finding also coincides with the previous empirical studies.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…Future studies should build upon the findings and the literature on parental relationships and child development by examining how the longitudinal associations between mother–child and father–child closeness and conflict are associated with adolescents' socioemotional and behavioral outcomes. Given that the impact of both the levels and rates of change of parent–child relationships on children's developmental outcomes is documented in prior research (Fosco et al, 2016; McElwain & Bub, 2018; Yan et al, 2018), it would be informative for future work to explore how the different patterns of parent–child relationships (e.g., lower levels of conflict at baseline with sharper increases in conflict over time versus higher initial levels of conflict with slower increases in conflict over time) are associated with children's psychosocial well‐being and behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Closeness is described as emotional and behavioral connections between parents and children, usually associated with warmth, support, trust, and communication (Laursen & Collins, 2009). Close parent–child relationships are positively associated with children's social competence and acceptance (McDowell & Parke, 2009), emotional well‐being (e.g., lower levels of loneliness; see Yan et al, 2018), and less engagement in risky behaviors (McElwain & Bub, 2018). Another central component of parent–child relationships is conflict , often defined as interpersonal interaction involving overt opposition and disputes (Smetana et al, 2006).…”
Section: Changes In Parent–child Relationships From Middle Childhood To Adolescencementioning
confidence: 99%
“…One of the most critical issues affecting mothers' mental health is the parent-child relationship [15,16]. A warm, intimate, and trusting relationship between parent and child is an essential factor in child development, and problems in this regard cause problems in the cognitive and emotional-behavioral development of the child [17][18][19][20]. Mothers of hearing-impaired children have difficulty building a positive mutual relationship between themselves and their children due to a lack of awareness of the new situation, the nature of the hearing loss, and the resulting psychological stress [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%